2005
DOI: 10.1128/iai.73.8.4888-4894.2005
|View full text |Cite
|
Sign up to set email alerts
|

Fsr-Independent Production of Protease(s) May Explain the Lack of Attenuation of an Enterococcus faecalis fsr Mutant Versus a gelE - sprE Mutant in Induction of Endocarditis

Abstract: An Enterococcus faecalis gelE insertion disruption mutant (TX5128), which produces neither gelatinase (GelE) nor the cotranscribed (in the wild type) serine protease (SprE), was found to be attenuated in a rat endocarditis model with a significant decrease in the endocarditis induction rate versus wild-type E. faecalis OG1RF (GelE ؉ , SprE ؉ ). TX5266, which has a nonpolar deletion in fsrB and, like TX5128, is phenotypically GelE ؊ under usual conditions, was also studied; fsrB is a homologue of agrB of staphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
56
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 36 publications
2
56
0
2
Order By: Relevance
“…In contrast, two subsequent studies did not show an increased prevalence of fsr in E. faecalis endocarditis and bloodstream isolates (11,23). In a rat endocarditis model, an E. faecalis mutant that did not produce gelatinase or serine protease had an endocarditis induction rate that was significantly reduced compared to that of wild-type E. faecalis (28). Further investigation is needed to elucidate the role of the fsr locus in the pathogenesis of E. faecalis infective endocarditis.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, two subsequent studies did not show an increased prevalence of fsr in E. faecalis endocarditis and bloodstream isolates (11,23). In a rat endocarditis model, an E. faecalis mutant that did not produce gelatinase or serine protease had an endocarditis induction rate that was significantly reduced compared to that of wild-type E. faecalis (28). Further investigation is needed to elucidate the role of the fsr locus in the pathogenesis of E. faecalis infective endocarditis.…”
mentioning
confidence: 84%
“…A quorum-sensing fsr locus has recently been described that regulates the transcription of a gelatinase gene (gelE) and a serine protease gene (sprE) and could contribute to E. faecalis virulence (22,26,28). The fsr locus regulates biofilm formation (14,20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Biofilm formation in E. faecalis has been reported to be influenced by various genes such as esp, initially reported by Toledo-Arana et al (2001). Gelatinase, which strongly influences virulence in models of peritonitis, endocarditis (Singh et al, 1998(Singh et al, , 2005, endophthalmitis (Engelbert et al, 2004) and in vitro translocation (Zeng et al, 2005), has been reported to influence biofilm formation (Mohamed et al, 2003(Mohamed et al, , 2004Hancock & Perego, 2004;Kristich et al, 2004). Other E. faecalis genes such as epa, atn (Mohamed et al, 2004), bop (Hufnagel et al, 2004), salA and salB (Mohamed et al, 2006) have also been shown to influence biofilms.…”
mentioning
confidence: 99%
“…Most strains of E. faecalis are gelE + , although only about 60 % of them have the fsr locus and are gelatinase producers by standard assay (Roberts et al, 2004). We have shown recently that all three fsr mutants (phenotypically GelE 2 SprE 2 by standard assay; Qin et al, 2000;Singh et al, 2005), as well as gelE mutants (GelE 2 SprE 2 ), showed decreased biofilm production (Mohamed et al, 2003(Mohamed et al, , 2004, a finding confirmed by Hancock & Perego (2004); the latter also showed that the introduction of fsrABC and fsrABC/gelE/ sprE into strain FA2-2 (GelE 2 , with point mutations in the fsrB and fsrC loci) resulted in gelatinase production and increased biofilm production (Hancock & Perego, 2004). However, our initial results had also suggested that fsr may have a role, in addition to activating gelatinase-mediated biofilm formation, as the fsr mutants formed slightly more biofilm than the gelatinase/serine protease double mutant TX5128 (Mohamed et al, 2004).…”
mentioning
confidence: 99%